Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1117/12.722040
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electrical conductance in a single porous SnO 2 nanoribbon

Abstract: Porous SnO 2 nanoribbons, with their width and thickness of around 20µm and 20nm, respectively, have been fabricated from the metallo-organic dimethyldineodecanoate tin using electrospinning and thermal decomposition techniques. The electrical conductance of one synthesized single ribbon has been measured using the two-probe method in atmosphere following a cycle of heating from 300 to 660K and subsequent cooling from 660K to 300K. During the heating, the conductance, G is not so sensitive to the temperature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several studies of SnO 2 doping with different metals to produce nanocrystals have been reported in recent years. [35][36][37] Sn 4? can be easily reduced to Sn 2?…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of SnO 2 doping with different metals to produce nanocrystals have been reported in recent years. [35][36][37] Sn 4? can be easily reduced to Sn 2?…”
Section: Introductionmentioning
confidence: 99%